Perancangan Robot Penjepit Barang Berbasis Mikrokontroler ATMega 8535 - Charles Ronald Harahap (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2009)
This paper discuses about how to design of things clamping Robot based on ATMega 8535. Based on human task is limited from power for lifting and moving things continuously, that is why, it is made another alternative for changing the task. It is made robot to move the things automatically. For designing robot, it is used microcontroller ATMega 8535 for controlling clamping robot. This robot is the wheeling robot kind which has a clamp in the front of the robot which will clamp the things if it is detected by sensor which is installed at the bottom of it’s clamping. Sensor is installed at the above robot which is function as wall detection in the front of it.